Physical properties and glycemic index studies of Singaraja white rice grown by conventional and organic methods in Denpasar Bali Indonesia - Andriania S.P.R.; Hamid M.H.N.A.; Sahrom M.S.; Yamin B.M. (Insight Society, 2024)
Indexed by SCOPUS